Bilar eller blåmesar? : rehabiliteringsvärdet i Umeås tätortsnära skogar - Lindén, Helena; Olofsson, Matilda (SLU/Dept. of Forest Ecology and Management, 2012)
Nature´s healing capacity is well known and is today an important asset in the protection against stress. Noise problems in cities and it´s green spaces are increasing which in turn provokes stress and in the long term can lead to cardiovascular diseases. To promote people’s health it is important that natural environments have good soundscapes, research show that visiting natural surroundings and listening to sounds of nature promote rehabilitation and relief stress. The purpose of this essay is to determine the value of rehabilitation in forests in Carlshem and Röbäck. By reviewing literature and through field studies, the forests have been evaluated according to criteria specified in earlier studies. Forests for rehabilitation should be bright and have a certain number of stems, age and height. The soundscape in the forests was valued both with noise measurement tools and through subjective evaluation. The results show that the forest in Carlshem is a good rehabilitation forest according to the forest criteria but the traffic noise is high which reduces its potential. The forest in Röbäck fulfills the subjective forest and has a good soundscape but does not fulfill the objective criteria. The subjective criteria are the most important one for rehabilitation forests and the forest in Röbäck can therefore be recommended to patients. Sufficient green areas with good soundscape in cities should be recognized as important to the citizen’s health. Hopefully future research will further examine the impact of noise in forests for rehabilitation.